The unveiling of life: Liturgy and the lure of kitsch - Cilliers, Johan (HTS teologiese studies, 2010)
This article probes the classic definition of religious aesthetics as related to the notions of beauty, goodness and truth. The phenomenon of kitsch, understood as simulation (or inversion) of beauty, goodness and truth, is taken cognisance of, especially in the light of contributions by Milan Kundera, Umberto Eco and Jean Baudrillard. The article briefly reflects on the liturgical consequences when kitsch manifests itself as simulated ‘beauty’, ‘goodness’ and ‘truth’ and concludes with some considerations regarding the characteristics of kitsch.